Delayed Diagnosis and Management of Traumatic Cervical Spine Subluxation - Elsissy, Joseph (J Orthop Case Rep, 2019)
INTRODUCTION: Traumatic cervical instability, which includes bilateral facet dislocation, unilateral facet dislocation, and bilateral facet perch or subluxation, is generally treated expeditiously. Treatment is focused on providing stability of the cervical spine and mitigating sequelae such as spinal cord injury, nerve injury, cervical deformity, chronic pain, and even death. Surgical stabilization of traumatic bilateral cervical facet subluxation is the norm. There is not much-published literature concerning late treatment of neglected cervical facet subluxations or dislocations. CASE REPORT: We present the case of a 53-year-old female who sustained cervical spine injury in 2010 after a single car motor vehicle accident. She did not seek immediate medical care but rather self-medicated with heroin, non-prescribed oral opiates and alcohol. She also wore a store-bought soft collar for support. She presented to our office in 2016 with persistent severe neck pain along with neck stiffness, fixed cervical flexion deformity, dysphagia, and left C6 radiculopathy. Plain radiographs demonstrated regional cervical kyphosis from C4 to C6 measuring 50°as well as autofusion at the C5/6 level. Cervical computed tomography (CT) confirmed traumatic ankylosis of C5/6 and anterolisthesis at C4/5. Cervical magnetic resonance imaging revealed multilevel cervical disc degeneration, moderate central stenosis at C4/5, and multilevel foraminal stenosis. We performed circumferential surgery: Anterior C5 and C6 corpectomy, placement of an expandable cage, and anterior C4 to C6 plating. This was followed by posterior decompression, lateral mass instrumentation, and fusion from C4-7. We were able to restore forward gaze, eliminate her dysphagia and the left C6 radiculopathy, and diminish the global neck pain. CONCLUSIONS: Neglect of unstable cervical injuries portends poor clinical results. In this case, the neglect was self-induced in part from the patient’s lifestyle, social situation, and lack of early access to healthcare. Despite the delayed treatment, surgical intervention was able to improve her quality of life and decrease her deformity.